Oral Presentations Abstracts: LIFE QUALITY OF PATIENTS WITH FACE TRANSPLANT - COVRIG, Vlad; BUDACU, Cristian; IOAN, Beatrice (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 The face is the feature which best distinguishes a person, the shape of it being influenced by the bone-structure of the skull. Facial trauma, known as maxillofacial trauma, is any physical trauma to the face that can involve soft and hard tissue having the potential to cause disfigurement. The last resort solution after major facial trauma, when conventional reconstruction techniques have failed is now represented by face transplant. The aim of this paper is to underline the life quality and psychological implication of patients that were face transplanted. Our material and method involved studying the most relevant medical literature for this issue and also using our personal experience of patient with face cancer that underwent radical oncological surgery followed by reconstruction. Based on these data we can conclude that face transplantation appears to decrease depression and to improve patient’s quality of life and societal reintegration. Also, in our opinion a very important factor involving the success of face transplantation is represented by the psychological outcomes of the patients, their follow up for a minimum 6 months period with regular psychological counselling sessions being very important. Furthermore, there is a critical need for modification of existing rating scales to allow effective assessment of face transplant candidates before and after transplantation.